A study of Malaysian students’ attitudes towards the Indonesian language and its speakers / Yoshiro Nishikata - Yoshiro , Nishikata (2019)
This study aims to identify Malaysians’ possible peculiar perceptions towards Bahasa Indonesia as well as Indonesians from the perspective of language attitudes. In order to examine their attitudes, a matched guise test and a questionnaire were conducted with two different groups of 50 Malaysian students. Consequently, the following two major findings were found: 1) Malaysian students seem to have generally positive language attitudes towards Bahasa Indonesia, and 2) Malaysian students seem to show a certain degree of ambiguity as far as their thoughts and behaviors towards Indonesians are concerned. The ambiguity was found in their generalized positive and negative attitudes towards Indonesians. It should be noted that this research has some limitations, for instance, the number of the participants might be low and only the evaluations by Malaysian students were taken into consideration.